"PM2.5 Airborne Particulates" Abstract - Jacobson, Jeron; Walters, Kristen; Pierce, Crispin (My University, 2014)
Abstract of "PM2.5 Airborne Particulates near Frac Sand Operations" by Crispin Pierce, Kristin Walters, Jeron Jacobson and Zachary Kroening (University of Wisconsin?Eau Claire). Published with permission of the Journal of Environmental Health (article accepted 29 Sept. 2014, publication Nov. 2015, in press, http://www.neha.org/JEH/).
Keywords: inhale; inhalation; EPA; Wisconsin; gas; oil; fracturing; hydraulic; dust; silica; particulate; PM2.5; sand; frac